PENGARUH E-COMMERCE, PENGELOLAAN KEUANGAN, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA UMKM PADA UMKM SEBERANG ULU II KOTA PALEMBANG - Nurul Hutami Ningsih; Kurnia Krisna Hari; Mia Kusumawaty; Sunia Saunina (Journal Economic Management and Business, 2026)
The problems in this study are the suboptimal use of e-commerce, unstructured financial management, and limited human resource competencies, which affect the performance of MSMEs. The objective of this study is to identify and analyze the three dependent variables on MSME performance. The research method used is associative research and quantitative methods. The population in this study was Micro, Small, and Medium Enterprises (MSMEs) in the food sector in Seberang Ulu II District, Palembang City. The sample used a purposive sampling technique, with 25 MSMEs and 67 respondents. The data used were primary data. The data collection method used a questionnaire. Data testing used validity and reality tests. The data analysis technique used was multiple linear regression analysis with the help of SPSS version 25. The results show that e-commerce affects MSME performance, financial management affects MSME performance, and human resource competency affects MSME performance.